Introduction to the Special Issue "Aesthetic Education and Screen Stories" - Iris Vidmar Jovanović; Ema Luna Lalić (European Journal of Analytic Philosophy)
This article is an introduction to the special issue of the European Journal of Analytic Philosophy dedicated to aesthetic education and philosophy of screen stories.